Neurotransmitter receptors and voltage-dependent Ca2+ channels encoded by mRNA from the adult corpus callosum. - Matute, C (1993)
The presence of mRNAs encoding neurotransmitter receptors and voltage-gated channels in the adult human and bovine corpus callosum was investigated using Xenopus oocytes. Oocytes injected with mRNA extracted from the corpus callosum expressed functional receptors to glutamate, acetylcholine, and serotonin, and also voltage-operated Ca2+ channels, all with similar properties in the two species studied. Acetylcholine and serotonin elicited oscillatory Cl- currents due to activation of the inositol phosphate-Ca2+ receptor-channel coupling system. Glutamate and its analogs N-methyl-D-aspartate (NMDA), kainate, quisqualate, and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) induced smooth currents. The non-NMDA responses showed a strong inward rectification at positive potentials and were potently blocked by 6,7-dinitroquinoxaline-2,3-dione, as observed for the AMPA/kainate glutamate receptors GLUR1 and GLUR3. Furthermore, in situ hybridization experiments showed that GLUR1 and GLUR3 mRNAs are present in corpus callosum cells that were labeled with antiserum to glial fibrillary acid protein and that, in primary cell cultures, had the morphology of type 2 astrocytes. These results indicate that glial cells in the adult corpus callosum possess mRNA encoding functional neurotransmitter receptors and Ca2+ channels. These molecules may provide a mechanism for glial-neuronal interactions.